Comparative Studies of the Physicochemical Properties of 3-Mercaptopyruvate Sulfurtransferase (3-MST) from Pennisetum glaucum (Millet) and Sorghum bicolor (Guinea corn) - O. S. , Adedeji; M. D. , Ezema; O. Y. , Adetuyi; B. O., Itakorode; R. E. , Okonji (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
3-Mercaptopyruvate sulfurtransferase (3-MST) is a cyanide detoxifying enzyme that helps in the detoxification of cyanide to a less toxic thiocyanate. 3-MST was purified from the seeds of Sorghum bicolor and Pennisetum glaucum. The enzyme was purified from the seeds by 80% ammonium sulphate precipitation and ion exchange chromatography on CM-Sephadex C-25. The Enzyme from Sorghum bicolor had a specific activity of 0.056 U/mg with a yield of 23.86 % while Pennisetum gluacum had specific activity and percentage yield of 0.0445 U/mg and 27.90% respectively. The Optimum pH of the enzyme from Sorghum bicolor and Pennisetum glaucum was observed at 6.0 and 8.0 respectively, while the optimum temperature was observed at 50 oC. The results of the inhibition studies revealed that there was no significant effect of the metal ions on the enzyme activity. The study confirmed the presence of 3-MST, a powerful cyanide detoxification mechanism in the seeds of Sorghum bicolor and Pennisetum glaucum.